2022
DOI: 10.3390/ani12091093
|View full text |Cite
|
Sign up to set email alerts
|

Early Detection of Respiratory Diseases in Calves by Use of an Ear-Attached Accelerometer

Abstract: Accelerometers (ACL) can identify behavioral and activity changes in calves. In the present study, we examined the association between bovine respiratory disease (BRD) and behavioral changes detected by an ear-tag based ACL system in weaned dairy calves. Accelerometer data were analyzed from 7 d before to 1 d after clinical diagnosis of BRD. All calves in the study (n = 508) were checked daily by an adapted University of Wisconsin Calf Scoring System. Calves with a score ≥ 4 and fever for at least two consecut… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
13
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(20 citation statements)
references
References 50 publications
0
13
0
Order By: Relevance
“…Decreased lying and active time in calves with diarrhea are evident 1 day before the visual diagnosis of the disease (Goharshahi et al, 2021). Differences in activity are observed up to 3 days prior to the peak day of respiratory disease in calves (Duthie et al, 2021; Ramezani Gardaloud et al, 2022). The results of the above studies were obtained using real‐time monitoring by an accelerometer‐based system.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Decreased lying and active time in calves with diarrhea are evident 1 day before the visual diagnosis of the disease (Goharshahi et al, 2021). Differences in activity are observed up to 3 days prior to the peak day of respiratory disease in calves (Duthie et al, 2021; Ramezani Gardaloud et al, 2022). The results of the above studies were obtained using real‐time monitoring by an accelerometer‐based system.…”
Section: Resultsmentioning
confidence: 99%
“…For calf 3, fever recurred throughout the experimental period due to respiratory disease despite frequent medical treatment. Ramezani Gardaloud et al, 2022). The results of the above studies were obtained using real-time monitoring by an accelerometer-based system.…”
Section: Lying Time Moving Distance and Healthmentioning
confidence: 99%
See 1 more Smart Citation
“…However, the best prediction model was only at −1 day prior to disease with a moderate accuracy of 71.5%, Se of 68.8% and an Sp of 72.4%. Gardaloud et al [ 64 ] reported a predictive model for BRD using behaviour data (obtained with an ear-attached 3D accelerometer) from −2 d and −3 d before symptoms with better Se (71.4%) and Sp (95.2%). Moreover, in Goharshahi et al [ 65 ], diarrheic calves had a longer lying time (64.8 min) −1 day prior to clinical identification compared with control calves (ear tag-based accelerometers; Smartbow GmbH).…”
Section: Technological Applications To Monitor Calves’ Health and Wel...mentioning
confidence: 99%
“…The diseased calf had significantly (P < 0.05) longer daily lying time than the other calves had on the À7, À5, À3, À2, and À1 day relative to the diagnosis day. The largest difference between the diseased calf and the other calves was 67 min/day on the day prior to diagnosis Gardaloud et al (2022). reported that diseased calves showed more daily inactive times from À5 days and longer daily lying time from…”
mentioning
confidence: 99%